Using phrasal verbs for natural English - Walter, Elizabeth, ....-; Woodford, Kate, ....- (Peaslake : Delta Publishing, 2011)
Every learner of English wants to develop fluent, natural English - understanding and using phrasal verbs is an essential part of this development. "Using Phrasal Verbs" not only helps learners to understand phrasal verbs, but also helps them learn when and how to use phrasal verbs successfully, to produce more natural-sounding English. "Using Phrasal Verbs": teaches students over 400 commonly used phrasal verbs; builds students' confidence in using phrasal verbs appropriately through thorough and varied practice; presents phrasal verbs in context and in a wide range of text types, including tweets, texts, web posts, e-mails, notes and newspaper articles; offers six review sections, each comprising sixty questions for students to test themselves on phrasal verbs learnt in the previous units; and, allows students to notice and practise aspects of stress and intonation through the conversational English examples on audio CD. It is suitable for Intermediate (B1) to Upper intermediate (B2) level.
With index and key